Reforma psiquiátrica e transição paradigmática no interior do estado de São Paulo - Mondoni, Daniel [UNESP]; Costa-Rosa, Abílio da [UNESP] (Universidade de Brasília (UnB), Instituto de Psicologia, 2010)
Este trabalho investiga o aspecto qualitativo da Reforma Psiquiátrica no interior do estado de São Paulo, por meio da análise dos discursos presentes no campo da Saúde Mental. Balizamo-nos no referencial da Atenção Psicossocial enquanto corpo teórico-prático e ético para transformação paradigmática em Saúde Mental. Como método, utilizamos entrevistas semi-dirigidas com coordenadores de CAPS e coordenadores municipais de Saúde Mental, e observações participantes, analisadas por meio do método dialético de análise de discurso. Foram encontradas três matrizes teóricas principais dos discursos (Psiquiatria Tradicional, Psiquiatria Preventivo-Comunitária, Atenção Psicossocial) coexistindo no espaço institucional. A vertente Preventivo-Comunitária mostrou-se bem instalada e superando técnica e teoricamente a Psiquiatria Tradicional, porém dificultando o avanço da Atenção Psicossocial em termos éticos.

This article investigates the Psychiatric Reform's qualitative aspect at São Paulo countryside by analyzing the discourses in the Mental Health field. This work is based on the Psycho-Social Attention referential as a theoretical, practical and ethical framework for the paradigmatic transformation on Mental Health. With respect to the methodology, we applied semi-directed interviews to CAPS coordinators and municipal Mental Health coordinators, and also performed participative observations, which were analyzed through the dialectical method of discourse analysis. It was observed three main theoretical discourses' streams (Traditional Psychiatry, Community-Preventive Psychiatry and Psycho-Social Attention) coexisting at the institution. Community-Preventive Psychiatry has been well established, but although it is overcoming some technical and theoretical constraints of Traditional Psychiatry, it is also imposing some difficulties to the ethical advances of Psycho-Social Attention.
Psychiatric Reform and paradigmatic transition at São Paulo countryside
Keywords: reforma psiquiátrica; paradigma; saúde mental; políticas públicas; psychiatric reform; paradigm; mental health; public policy